GIS FOR AN ESTIMATION OF INFLUENCE FACTORS OF THE LANDSLIDE FORMATION ON THE ROUTE SIMFEROPOL-YALTA-SEVASTOPOL - FRINDT, M. (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2025)
In this paper the method of the use GIS is offered for an estimation of influence factors on landslide formation. The conceptual model is developed. The structure of a database and process of surfaces creation of natural and technogenic factors influence is shown.